1997
DOI: 10.1055/s-0038-1657658
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Development of Mural Thrombi in Chronic Experimental Aneurysms in Sheep

Abstract: SummaryObservations were made on mural thrombi in experimental venous pouch aneurysms in sheep. Thrombi associated with mural tears and dissection consisted predominantly of laminated fibrin masking the earlier platelet deposition and infiltrating the wall to some extent. Thrombus growth was associated with platelet masses of Zahn and secondary fibrin deposition. Intervening spaces contained a variable quantity of coagulated plasma, fibrin mesh, leucocytes, disintegrating red cells and platelets rather than re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Multilayering of dense fibrin and RBC areas into Zahn lines or circular spaces was recorded, corresponding to the successive layers of thrombus formed with time. 17 Two of the 3 autopsy cases (cases 8 and 2), harvested at 2.5 and 27 months, respectively, presented deficient healing similar to the findings in failed implants retrieved at surgery. These stent-grafts were encapsulated in unorganized thrombotic material.…”
Section: Healing Around Stent-graftssupporting
confidence: 53%
“…Multilayering of dense fibrin and RBC areas into Zahn lines or circular spaces was recorded, corresponding to the successive layers of thrombus formed with time. 17 Two of the 3 autopsy cases (cases 8 and 2), harvested at 2.5 and 27 months, respectively, presented deficient healing similar to the findings in failed implants retrieved at surgery. These stent-grafts were encapsulated in unorganized thrombotic material.…”
Section: Healing Around Stent-graftssupporting
confidence: 53%
“…These studies concluded that aneurysm formation was due to a weakness of the vascular wall. Venous aneurysms and thrombus formation has been suggested in an experimental model (10). Several case reports suggest that progressive aneurysmal dilation of the pulmonary arteries can occur over a period of several years (9).…”
Section: Discussionmentioning
confidence: 99%
“…None of the small animal aneurysm models reproduces the complex intraluminal thrombosis that is a prominent feature of almost all human AAAs, often occupying the bulk of the aneurysm sac. Its structure in the human disease is quite unusual (Figs 1 and 2) because, while the thrombus on the luminal aspect is a typical ®brin mesh with canaliculi and many in¯ammatory cells, the deeper juxtamural thrombus is often formed from many layers of organized thrombus characterized by few cells, a ®brinous extracellular matrix, lipid accumulation and occasional calci®cation 37,38 . Some degree of intraluminal thrombosis may be present in certain small animal models, but when this occurs it seems to consist only of ®brinous deposits on the damaged tunica intima 22 and not the complex organized thrombus characteristic of the human pathology.…”
Section: Medial and Adventitial Injury Aneurysm Modelsmentioning
confidence: 99%